2009
DOI: 10.1248/cpb.57.439
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cannabinoid Analog as a New Type of Designer Drug in a Herbal Product

Abstract: A new type of designer drug, a cannabinoid analog (1), was found in a herbal product distributed on the illegal drug market in Japan in expectation of its narcotic effect. The structure of 1 was identified by LC-MS, GC-MS, high-resolution MS, and NMR analyses. Compound 1 showed a molecular weight of 332, and accurate mass measurement exhibited its elemental composition to be C 22 H 36 O 2 . Together, the mass and NMR spectrometric data revealed that 1 was (1RS,3SR)-3-[4-(1,1-dimethyloctyl)-2-hydroxyphenyl]cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
113
0
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 12 publications
1
113
0
5
Order By: Relevance
“…Beginning in October 2012, new type of synthetic cannabinoids, a structural modification of compounds from 3-naphthoylindole series [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] has begun to be seized by police regularly, on the territory of Russia and Belarus.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in October 2012, new type of synthetic cannabinoids, a structural modification of compounds from 3-naphthoylindole series [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] has begun to be seized by police regularly, on the territory of Russia and Belarus.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous occurrences of these 'designer drugs' were detected in many countries including Russia and Belarus. These compounds are basically indole derivatives such as 3-naphthoylindoles, 3-phenylacetylindoles, 3-benzoylindoles and 3-adamantoylindoles [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We have identified that since the summer 2011 most popular compounds, from the class, were: 'TMCP-018' (2), parent 3-(2,2,3,3-tetramethylcyclopropanecarbonyl)indole (1) and the other derivatives thereof (3)(4)(5)(6)(7), as well as {N-[3-(2-methoxyethyl)-4,5-dimethylthiazol-2(3H)-ylidene]-2,2,3,3-tetramethylcyclopropanecarboxamide} (8) ('A-836,339'), a thiazolidene analog of the compounds under discussion (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…72 Esses compostos possuem estruturas químicas variadas, que vão desde derivados clássicos, que apresentam o anel dibenzopirano característico até estruturas não clássicas, derivadas do indol, indeno, pirrol, pirazol e cicloexanol, porém compartilhando a alta afinidade pelos receptores canabinoides. 18 As estruturas químicas de alguns derivados com ação canabinomimética estão representadas na Figura 7.…”
Section: Derivados Canabinoidesunclassified
“…Para a detecção foram utilizadas a cromatografia líquida de ultra eficiência acoplada ao espectrômetro de massas (CLUE/ESI-EM) e detector de arranjo de diodos (CLUE/DAD), além de CG/EM. 18,72 Alguns derivados canabinoides foram analisados no sangue, utilizando CG/EM após extração em fase sólida e silanização. 74 Foi conduzido um estudo para a detecção de metabólitos de JWH-018 na urina, em que os metabólitos se conjugaram com ácido glicurônico e foram detectados por CG e CLAE/EM/EM.…”
Section: Derivados Canabinoidesunclassified